Development Of Integrated Learning Tools For Immersed Model To Make Students Environmentalists - Markus Sampe; Silvester Taneo; Sofia Godeliva Un Lala; Rista Aprilliya Devi; Martha Kota; Chalvin Nubrihas; Hafiza Uma Leba (Dinasti Publisher, 2024)
Integrated learning immersed model is learning that is in accordance with the interests of students and can grow students' love for the field of interest. Integrated learning immersed model in elementary school begins with students' interest in a field so that students have the urge in themselves to learn more about the field so that students become experts in the field of their interest, this research was conducted to provide solutions related to environmental problems in Indonesia through immersed learning model. The formulation of the problem in this study is how the effectiveness of immersed model learning tools to foster a love for the environment? The purpose of this research is to describe the effectiveness of immersed model learning tools. This research method is R&D (Research and Develop) with 4D design, namely define, design, develop and dessiminate. The result of the research is that the integrated learning device immersed model is declared feasible in terms of the validity of the learning device. Practical to use is indicated by a high percentage of learning implementation, obstacles that arise do not significantly affect learning, and student responses to integrated learning immersed models are positive and good. The immersed model integrated learning device is effective to use in terms of learning outcomes test results that have increased significantly.